Sexuality and HIV/AIDS Profiles among Fisherfolk in Kainji Lake Basin (Global Journal of Medical Research, 2013)
HIV/AIDS is spread through high risk behaviors, fishing communities are among the social groups that are most vulnerable to HIV/AIDS infection because of their lifestyle and the way they conduct their fishing activities. The objective is to examine sexual behavioral practices of fisher folk and HIV/AIDS vulnerability profile in the fisheries sector of Kainji Lake Basin. A twostage random sampling procedure was used to select 400 respondents for this study. Kainji Lake Basin was stratified into eight strata based on Kainji Lake Management and Conservation Unit (KLMCU) classification. The data were subjected to descriptive, and Mann Whitney U. The findings revealed that only 28.3% of the respondents agreed that they became sexually active between ages between 10 -15. 53.9% had two or more sexual partners. Only 7.0% of the respondents said they have had extra marital sex. 20.2% of the respondents said condom can be accessed in their community. Only 6.5% had use condom in the past 12 months.
Keywords: sex; condom; fisher folk; fishing communities; disease and hiv/aids